Perovskite solar cell and preparation method thereof
Patent Information
- Application Number
- CN202611041970.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]本发明的目的在于提供一种钙钛矿太阳能电池及其制备方法,以解决或改善上述技术问题
本发明提供的钙钛矿太阳能电池,在基底表面特定设置NCQDs-TiO2电子传输层,NCQDs-TiO2电子传输层中含有由TiO2与掺杂N的碳量子点形成的Ti-O-C共价键。
Smart Images

Figure CN122892373A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of perovskite solar cell technology, and more specifically, to a perovskite solar cell and its fabrication method. Background Technology
[0002] Titanium dioxide (TiO2) has become the most commonly used electron transport layer material in perovskite solar cells due to its suitable energy level positions, good chemical stability, and low cost. The TiO2 electron transport layer extracts photogenerated electrons from the perovskite light-absorbing layer and efficiently transports them to the conductive substrate, while simultaneously blocking the transport of holes to the cathode, thereby reducing carrier recombination losses and improving the photoelectric conversion efficiency of the device. However, traditional TiO2 electron transport layers suffer from problems in practical applications, such as low electron mobility, numerous surface defects, poor energy level matching, and limited spectral response. These problems collectively limit the performance and stability of perovskite solar cells, becoming a key technological bottleneck restricting their commercial application.
[0003] In view of this, the present invention is proposed. Summary of the Invention
[0004] The purpose of this invention is to provide a perovskite solar cell and its preparation method, so as to solve or improve the above-mentioned technical problems.
[0005] This invention can be implemented as follows: In a first aspect, the present invention provides a perovskite solar cell, the perovskite solar cell including an NCQDs-TiO2 electron transport layer disposed on the surface of a substrate, the NCQDs-TiO2 electron transport layer containing Ti-OC covalent bonds formed by TiO2 and N-doped carbon quantum dots; In the NCQDs-TiO2 electron transport layer, the mass ratio of N-doped carbon quantum dots to TiO2 is 0.1:100 to 5:100.
[0006] In an optional embodiment, the NCQDs-TiO2 electron transport layer also has at least one of the following characteristics: Feature 1: In N-doped carbon quantum dots, the amount of N doping is 5wt%~15wt%.
[0007] Feature 2: The thickness of the NCQDs-TiO2 electron transport layer is 20nm~100nm.
[0008] In an optional embodiment, the perovskite solar cell further includes a perovskite light-absorbing layer, a hole transport layer, and a metal electrode. The perovskite light-absorbing layer is disposed on the surface of the NCQDs-TiO2 electron transport layer away from the substrate; the hole transport layer is disposed on the surface of the perovskite light-absorbing layer away from the NCQDs-TiO2 electron transport layer; and the metal electrode is disposed on the surface of the hole transport layer away from the perovskite light-absorbing layer.
[0009] In an optional embodiment, the perovskite solar cell has at least one of the following characteristics: Feature 3: The short-circuit current density of perovskite solar cells is not less than 22.7 mA / cm². 2 ; Feature 4: The open-circuit voltage of perovskite solar cells is not less than 1.08V; Feature 5: The fill factor of the perovskite solar cell is not less than 0.74; Feature 6: The photoelectric conversion efficiency of perovskite solar cells is not less than 18%.
[0010] In a second aspect, the present invention provides a method for preparing a perovskite solar cell as described in any of the foregoing embodiments, comprising the following steps: coating a TiO2 precursor solution modified with nitrogen-doped carbon quantum dots onto a substrate surface, followed by solvent removal and annealing.
[0011] In an optional embodiment, the coating is performed by spin coating, with a spin coating speed of 2800 r / min to 3200 r / min and a spin coating time of 25 s to 35 s.
[0012] In an optional embodiment, the solvent is removed by heating at a temperature of 140°C to 160°C for a duration of 8 to 12 minutes.
[0013] In an optional embodiment, the annealing temperature is 150℃~250℃ and the annealing time is 30min~90min.
[0014] In an optional embodiment, the preparation of the nitrogen-doped carbon quantum dot modified TiO2 precursor solution includes: dispersing nitrogen-doped carbon quantum dots in the TiO2 precursor solution.
[0015] In an optional embodiment, dispersing nitrogen-doped carbon quantum dots in a TiO2 precursor solution includes: mixing the nitrogen-doped carbon quantum dot solution with the TiO2 precursor solution and sonicating.
[0016] In an optional embodiment, the solute in the TiO2 precursor solution includes at least one of isopropyl titanate and tetraethyl titanate, and the solvent includes at least one of ethanol and isopropanol.
[0017] In an optional embodiment, the concentration of the solute in the TiO2 precursor solution is 0.12 mol / L to 0.18 mol / L.
[0018] In an optional embodiment, the nitrogen-doped carbon quantum dot solution is an aqueous solution of nitrogen-doped carbon quantum dots, and the ratio of nitrogen-doped carbon quantum dots to water is from 0.5 mg:1 mL to 5 mg:1 mL.
[0019] In an optional embodiment, the preparation of nitrogen-doped carbon quantum dots includes: reacting a carbon source and a nitrogen source in the presence of water, dialyzing the reaction product, and drying it.
[0020] In an optional embodiment, the carbon source includes at least one of citric acid and o-phenylenediamine.
[0021] In an optional embodiment, the nitrogen source includes at least one of urea and ethylenediamine.
[0022] In an optional embodiment, the mass ratio of carbon source to nitrogen source is 1:0.4 to 1:0.6.
[0023] In an optional embodiment, the reaction temperature of the carbon source and nitrogen source is 180℃~220℃, and the reaction time is 5h~10h.
[0024] The beneficial effects of this invention include: The perovskite solar cell provided by the present invention has an NCQDs-TiO2 electron transport layer specifically disposed on the substrate surface. The NCQDs-TiO2 electron transport layer contains Ti-OC covalent bonds formed by TiO2 and N-doped carbon quantum dots.
[0025] By introducing nitrogen-doped carbon quantum dots (NCQDs) into the TiO2 electron transport layer, NCQDs exhibit excellent upconversion luminescence properties, converting near-infrared light into visible light, thus broadening the spectral response range of the perovskite absorption layer and improving light utilization efficiency. The oxygen-containing functional groups such as carboxyl (-COOH) and hydroxyl (-OH) groups on the NCQD surface undergo condensation reactions with titanium atoms on the TiO2 surface, releasing water molecules and forming Ti-OC bonds. This covalent bond connection not only enhances the interfacial bonding strength but also constructs efficient electron transport channels, reducing interfacial resistance and improving electron mobility. Furthermore, the Ti-OC bond can effectively regulate the energy level arrangement between the TiO2 electron transport layer and the perovskite layer, making it more compatible with the conduction band position of the perovskite material, lowering the electron injection barrier, and promoting the efficient extraction of photogenerated electrons. In addition, the abundant functional groups (such as amino and carboxyl groups) on the surface of NCQDs can chemically bond or coordinate with uncoordinated lead ions, iodine vacancies and other defect sites on the perovskite grain boundaries and surface, fill defect states, reduce nonradiative recombination centers, thereby suppressing carrier recombination loss and improving the open-circuit voltage and fill factor of the device. Attached Figure Description
[0026] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0027] Figure 1 This is a comparison chart of the test results of Example 4 and Comparative Example 1. Detailed Implementation
[0028] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0029] The perovskite solar cell and its preparation method provided by the present invention will be described in detail below.
[0030] The present invention provides a perovskite solar cell, which includes an NCQDs-TiO2 electron transport layer disposed on the surface of a substrate, wherein the NCQDs-TiO2 electron transport layer contains Ti-OC covalent bonds formed by TiO2 and N-doped carbon quantum dots.
[0031] By introducing N-doped carbon quantum dots (NCQDs) into the TiO2 electron transport layer, NCQDs exhibit excellent upconversion luminescence properties, enabling the conversion of near-infrared light into visible light, thus broadening the spectral response range of the perovskite light-absorbing layer and improving light utilization efficiency.
[0032] Oxygen-containing functional groups such as carboxyl (-COOH) and hydroxyl (-OH) groups on the surface of NCQDs undergo condensation reactions with titanium atoms on the TiO2 surface, releasing water molecules and forming Ti-OC bonds. This covalent bonding not only enhances interfacial bonding strength but also constructs efficient electron transport channels, reducing interfacial resistance and improving electron mobility. Furthermore, the Ti-OC covalent bonds can effectively regulate the energy level arrangement between the TiO2 electron transport layer and the perovskite layer, making it more compatible with the conduction band position of the perovskite material, lowering the electron injection barrier, and promoting efficient extraction of photogenerated electrons. In addition, the abundant functional groups (such as amino and carboxyl groups) on the NCQD surface can chemically bond or coordinate with uncoordinated lead ions, iodine vacancies, and other defect sites at perovskite grain boundaries and surfaces, filling defect states, reducing non-radiative recombination centers, thereby suppressing carrier recombination losses and improving the open-circuit voltage and fill factor of the device.
[0033] In some alternative implementations, the mass ratio of N-doped carbon quantum dots to TiO2 in the NCQDs-TiO2 electron transport layer can be from 0.1:100 to 5:100, such as 0.1:100, 0.5:100, 1:100, 1.5:100, 2:100, 2.5:100, 3:100, 3.5:100, 4:100, 4.5:100, or 5:100, or other values within the range of 0.1:100 to 5:100.
[0034] If the mass ratio of N-doped carbon quantum dots to TiO2 is less than 0.1:100 (e.g., 0.05:100), it is not conducive to defect passivation, energy level modulation, and improvement of conductivity. If the mass ratio of N-doped carbon quantum dots to TiO2 is greater than 5:100 (e.g., 10:100), new recombination centers will be formed, electron mobility will decrease, energy level mismatch will occur, and stability will deteriorate.
[0035] In some preferred embodiments, the mass ratio of N-doped carbon quantum dots to TiO2 is 0.1:100 to 3:100; in some more preferred embodiments, the mass ratio of N-doped carbon quantum dots to TiO2 is 0.5:100 to 3:100; in some even more preferred embodiments, the mass ratio of N-doped carbon quantum dots to TiO2 is 0.5:100 to 2:100; and in some even more preferred embodiments, the mass ratio of N-doped carbon quantum dots to TiO2 is 1:100.
[0036] In some alternative embodiments, the amount of N doped in the N-doped carbon quantum dots can be 5wt% to 15wt%, such as 5wt%, 8wt%, 10wt%, 12wt% or 15wt%, or other values in the range of 5wt% to 15wt%.
[0037] The nitrogen (N) doping in the aforementioned carbon quantum dots can regulate the Fermi level of the carbon dots, increase the on-state voltage, provide efficient defect passivation, and enhance conductivity. However, in N-doped carbon quantum dots, if the N doping amount is less than 5 wt%, defect passivation fails, the bandgap regulation effect is small, and the conductivity improvement is limited. If the N doping amount is greater than 15 wt%, the carbon dot structure is destroyed, conductivity decreases, and severe aggregation and recombination centers are generated.
[0038] In some alternative implementations, the thickness of the NCQDs-TiO2 electron transport layer can be 20nm to 100nm, such as 20nm, 50nm, 80nm or 100nm, or other values within the range of 20nm to 100nm.
[0039] If the thickness of the NCQDs-TiO2 electron transport layer is too thin, the coverage is insufficient, the leakage current increases dramatically, and the NCQDs modification cannot make up for the physical coverage defects; if the thickness of the NCQDs-TiO2 electron transport layer is too thick, the series resistance increases.
[0040] In some alternative implementations, the substrate may exemplary include FTO conductive glass, and may also include ITO conductive glass, etc.
[0041] In some alternative embodiments, the perovskite solar cell further includes a perovskite light-absorbing layer; the perovskite light-absorbing layer is disposed on the surface of the NCQDs-TiO2 electron transport layer on the side away from the substrate.
[0042] The perovskite light-absorbing layer may, by way of example, include at least one of the following: CH3NH3PbI3 light-absorbing layer, MAPbI3 light-absorbing layer, and FAPbI3 light-absorbing layer.
[0043] The thickness of the perovskite light-absorbing layer can be 400nm~600nm, such as 400nm, 450nm, 500nm, 550nm or 600nm, or other values in the range of 400nm~600nm.
[0044] In some alternative embodiments, the perovskite solar cell may further include a hole transport layer; the hole transport layer is disposed on the surface of the perovskite light-absorbing layer on the side away from the NCQDs-TiO2 electron transport layer.
[0045] The hole transport layer may, by way of example, include at least one of the Spiro-OMeTAD hole transport layer and PTAA hole transport layer, PEDOT:PSS hole transport layer and P3HT hole transport layer.
[0046] The thickness of the hole transport layer can be 100nm~200nm, such as 100nm, 150nm or 200nm, or other values in the range of 100nm~200nm.
[0047] In some alternative embodiments, the perovskite solar cell may further include a metal electrode disposed on the surface of the hole transport layer on the side away from the perovskite light-absorbing layer.
[0048] Metal electrodes may, by way of example, include at least one of gold electrodes, silver electrodes, and aluminum electrodes.
[0049] The thickness of the metal electrode can be 70nm~80nm, such as 70nm, 75nm or 80nm, or other values within the range of 70nm~80nm.
[0050] In some optional embodiments, the short-circuit current density of the perovskite solar cell provided by the present invention is not less than 22.7 mA / cm². 2 For example, it can be 22.7 mA / cm 2 ~24.2mA / cm 2 .
[0051] In some optional embodiments, the open-circuit voltage of the perovskite solar cell provided by the present invention is not less than 1.08V, for example, it can be 1.08V~1.14V.
[0052] In some optional embodiments, the fill factor of the perovskite solar cell provided by the present invention is not less than 0.74, for example, it can be 0.74 to 0.78.
[0053] In some optional embodiments, the photoelectric conversion efficiency of the perovskite solar cell provided by the present invention is not less than 18%, for example, it can be 18.1% to 21.5%.
[0054] Accordingly, the present invention also provides a method for preparing the above-mentioned perovskite solar cell, comprising the following steps: coating a TiO2 precursor solution modified with nitrogen-doped carbon quantum dots onto the substrate surface, then removing the solvent and annealing.
[0055] In some optional embodiments, the substrate may be pretreated before coating with the nitrogen-doped carbon quantum dot-modified TiO2 precursor solution to remove surface organic contaminants and improve surface wettability. For example, the pretreatment may include cleaning the substrate followed by ultraviolet ozone treatment. The cleaning agents may include, for example, deionized water, acetone, isopropanol, etc., and the cleaning method may be ultrasonic cleaning.
[0056] In some optional embodiments, spin coating can be used. The spin coating speed can be between 2800 r / min and 3200 r / min, such as 2800 r / min, 2900 r / min, 3000 r / min, 3100 r / min, or 3200 r / min, or other values within the range of 2800 r / min to 3200 r / min. The spin coating time can be between 25 s and 35 s, such as 25 s, 28 s, 30 s, 32 s, or 35 s, or other values within the range of 25 s to 35 s.
[0057] In some optional embodiments, solvent removal can be achieved by heating. The heating temperature can be between 140°C and 160°C, such as 140°C, 145°C, 150°C, 155°C, or 160°C, or other values within the range of 140°C to 160°C. The heating time can be between 8 min and 12 min, such as 8 min, 9 min, 10 min, 11 min, or 12 min, or other values within the range of 8 min to 12 min.
[0058] In some optional embodiments, the annealing temperature can be 150℃~250℃, such as 150℃, 180℃, 200℃, 220℃ or 250℃, or other values within the range of 150℃~250℃. The annealing time can be 30min~90min, such as 30min, 40min, 50min, 60min, 70min, 80min or 90min, or other values within the range of 30min~90min.
[0059] Annealing under the above conditions allows the quantum dots to form Ti-OC covalent bonds at the TiO2 interface. If the annealing temperature is below 150℃, TiO2 is prone to becoming completely amorphous, affecting electron mobility; if the annealing temperature is above 250℃, NCQDs are prone to complete decomposition.
[0060] In some alternative embodiments, the preparation of the nitrogen-doped carbon quantum dot-modified TiO2 precursor solution may include dispersing nitrogen-doped carbon quantum dots in the TiO2 precursor solution. In practice, the nitrogen-doped carbon quantum dot solution may be mixed with the TiO2 precursor solution and then sonicated.
[0061] The nitrogen-doped carbon quantum dot solution is an aqueous solution of nitrogen-doped carbon quantum dots. The ratio of nitrogen-doped carbon quantum dots to water can be from 0.5 mg:1 mL to 5 mg:1 mL, such as 0.5 mg:1 mL, 1 mg:1 mL, 2 mg:1 mL, 3 mg:1 mL, 4 mg:1 mL or 5 mg:1 mL, or other values within the range.
[0062] The solute in the TiO2 precursor solution may, by way of example, include at least one of isopropyl titanate and tetraethyl titanate, and the solvent may, by way of example, include at least one of ethanol and isopropanol.
[0063] In the above TiO2 precursor solution, the concentration of the solute can be 0.12 mol / L to 0.18 mol / L, such as 0.12 mol / L, 0.15 mol / L or 0.18 mol / L, or other values within the range of 0.12 mol / L to 0.18 mol / L.
[0064] In specific operations, the TiO2 precursor solution and NCQDs aqueous solution (0.5 ~ 5 mg / ml) can be mixed at a mass ratio of N-doped carbon quantum dots to TiO2 of 0.1:100 to 5:100, and ultrasonically treated for 25 min to 35 min to uniformly disperse NCQDs in the TiO2 precursor solution, thus obtaining the NCQDs-modified TiO2 precursor solution.
[0065] The mass ratio of the TiO2 precursor solution to the NCQDs aqueous solution corresponds to the mass ratio of N-doped carbon quantum dots to TiO2. Within the above range, the mass ratio of N-doped carbon quantum dots to TiO2 in the NCQDs-TiO2 electron transport layer can be from 0.1:100 to 5:100.
[0066] In some alternative embodiments, the preparation of the nitrogen-doped carbon quantum dots may include: reacting a carbon source and a nitrogen source in the presence of water, dialysis of the reaction products, and drying.
[0067] The carbon source may, by way of example, include at least one of citric acid and o-phenylenediamine.
[0068] The nitrogen source may, by way of example, include at least one of urea and ethylenediamine.
[0069] The mass ratio of carbon source to nitrogen source can be from 1:0.4 to 1:0.6, such as 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7 or 1:0.8, or other values within the range of 1:0.2 to 1:0.8.
[0070] The mass ratio of carbon source to nitrogen source affects the amount of N doping in quantum dots. Within the above range, the amount of N doping can be 5wt% to 15wt%.
[0071] The reaction temperature of the carbon source and nitrogen source can be 180℃~220℃, such as 180℃, 190℃, 200℃, 210℃ or 220℃, or other values within the range of 180℃~220℃.
[0072] The reaction time can be 5h to 10h, such as 5h, 6h, 7h, 8h, 9h or 10h, or other values within the range of 5h to 10h.
[0073] Under the above reaction conditions, the reaction mechanism of the carbon source and nitrogen source is essentially a "polymerization-carbonization" process in which small organic molecules are successively transformed into nitrogen-containing polymers, nitrogen-containing heterocyclic aromatization, and nitrogen-doped carbon cores. The carbon source and nitrogen source undergo amidation polymerization, followed by aromatization and rearrangement, ultimately forming a surface rich in pyridine / pyrrole nitrogen (passivated active sites).
[0074] In practice, carbon and nitrogen sources are mixed at a mass ratio of 1:0.2 to 1:0.8 and dissolved in 15 mL to 25 mL of deionized water. The mixture is then transferred to a high-pressure reactor lined with polytetrafluoroethylene (PTFE) and reacted at 180 °C to 220 °C for 5 to 10 hours. After the reaction is complete, the mixture is allowed to cool naturally to room temperature to obtain a dark brown aqueous solution of nitrogen-doped carbon quantum dots. Solid nitrogen-doped carbon quantum dot powder is obtained through dialysis and freeze-drying.
[0075] Further, taking the CH3NH3PbI3 absorber layer of perovskite as an example, this layer can be prepared by a one-step spin-coating method, for example, as follows: Dissolve 461 mg PbI2 and 159 mg CH3NH3I in 1 mL of a mixed solvent of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) (volume ratio of 6.5:3.5 to 7.5:2.5), and stir overnight to obtain a perovskite precursor solution. In a nitrogen glove box, spin-coat the perovskite precursor solution at a speed of 3800 r / min to 4200 r / min for 35 s to 45 s. At the 25th second of spin-coating, rapidly add 180 μL to 220 μL of chlorobenzene as an anti-solvent. After spin-coating, immediately transfer the sample to a hot plate at 95℃ to 100℃ for annealing for 10 min to 15 min to obtain a dark brown perovskite film.
[0076] Furthermore, taking Spiro-OMeTAD hole transport layer as an example, this layer can also be prepared using a one-step spin-coating method. For instance, the following procedure can be followed: Dissolve 72.3 mg of Spiro-OMeTAD in 1 mL of chlorobenzene, add 28.8 μL of 4-tert-butylpyridine and 17.5 μL of acetonitrile solution of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) (520 mg / mL) to prepare a hole transport layer solution. Spin-coat at 3800 r / min for 25 s to 35 s to obtain the hole transport layer.
[0077] Furthermore, taking gold electrodes as an example, they can be prepared by vapor deposition.
[0078] It should be noted that the perovskite light-absorbing layer, hole transport layer and metal electrode mentioned above can all refer to the conventional settings in the art. For example, the selection of materials and the preparation methods and conditions are not specifically limited.
[0079] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0080] Example 1 This embodiment provides a perovskite solar cell, which includes a substrate, an NCQDs-TiO2 electron transport layer, a perovskite absorber layer, a hole transport layer, and a back electrode, which are sequentially disposed from the FTO conductive glass substrate side to the back electrode side.
[0081] The fabrication method of this perovskite solar cell includes: S1: Substrate pretreatment.
[0082] The FTO conductive glass was ultrasonically cleaned with deionized water, acetone, and isopropanol for 15 minutes each, then dried with nitrogen, and finally treated in an ultraviolet ozone treatment instrument for 15 minutes.
[0083] S2: Preparation of NCQDs-TiO2 electron transport layer.
[0084] S2-1: Preparation of nitrogen-doped carbon quantum dots: 1 g of citric acid and 0.5 g of urea were dissolved in 20 mL of deionized water and transferred to a high-pressure reactor lined with polytetrafluoroethylene. The mixture was reacted at 200 °C for 8 h. After the reaction was complete, the mixture was allowed to cool naturally to room temperature to obtain a dark brown aqueous solution of nitrogen-doped carbon quantum dots. Solid nitrogen-doped carbon quantum dot powder (10 wt% N doping) was obtained by dialysis and freeze-drying.
[0085] S2-2: Preparation of TiO2 precursor solution modified with nitrogen-doped carbon quantum dots: The TiO2 precursor solution (ethanol solution of isopropyl titanate, concentration of 0.15 mol / L) and the aqueous solution of nitrogen-doped carbon quantum dots (concentration of 2 mg / ml) were mixed at a mass ratio of 100:5 and ultrasonically treated for 30 min to uniformly disperse the nitrogen-doped carbon quantum dots in the TiO2 precursor solution.
[0086] S2-3: Preparation of the electron transport layer: A nitrogen-doped carbon quantum dot-modified TiO2 precursor solution was spin-coated onto the FTO substrate obtained in step S1 at a speed of 3000 r / min for 30 s, followed by pre-calcination on a hot plate at 150 °C for 10 min to remove the solvent. Subsequently, it was annealed in a muffle furnace at 200 °C for 60 min to obtain a dense NCQDs-TiO2 electron transport layer with a thickness of approximately 50 nm.
[0087] S3: Prepare a perovskite light-absorbing layer.
[0088] 461 mg PbI₂ and 159 mg CH₃NH₃I were dissolved in 1 mL of a mixed solvent of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) (volume ratio 7:3), and stirred overnight to obtain a perovskite precursor solution. In a nitrogen glove box, the perovskite precursor solution was spin-coated at 4000 rpm for 40 s. At the 25th second of spin-coating, 200 μL of chlorobenzene was rapidly added dropwise as an anti-solvent. After spin-coating, the sample was immediately transferred to a hot plate at 100 °C and annealed for 10 min to obtain a dark brown perovskite film with a thickness of approximately 450 nm.
[0089] S4: Prepare the hole transport layer.
[0090] 72.3 mg of spiro-OMeTAD was dissolved in 1 mL of chlorobenzene, and 28.8 μL of 4-tert-butylpyridine and 17.5 μL of acetonitrile solution of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) (520 mg / mL) were added to prepare a hole transport layer solution. The solution was spin-coated at 4000 rpm for 30 s to obtain a hole transport layer with a thickness of approximately 150 nm.
[0091] S5: Prepare the metal electrode.
[0092] An 80 nm thick gold electrode was deposited on the surface of the hole transport layer using a thermal evaporation method.
[0093] Example 2 The difference between this embodiment and Embodiment 1 is that the mass ratio of the TiO2 precursor solution to the aqueous solution of nitrogen-doped carbon quantum dots is 100:3.
[0094] Example 3 The difference between this embodiment and Embodiment 1 is that the mass ratio of the TiO2 precursor solution to the aqueous solution of nitrogen-doped carbon quantum dots is 100:2.
[0095] Example 4 The difference between this embodiment and Embodiment 1 is that the mass ratio of the TiO2 precursor solution to the aqueous solution of nitrogen-doped carbon quantum dots is 100:1.
[0096] Example 5 The difference between this embodiment and Embodiment 1 is that the mass ratio of the TiO2 precursor solution to the aqueous solution of nitrogen-doped carbon quantum dots is 100:0.5.
[0097] Example 6 The difference between this embodiment and Embodiment 1 is that the mass ratio of the TiO2 precursor solution to the aqueous solution of nitrogen-doped carbon quantum dots is 100:0.1.
[0098] Example 7 This embodiment provides a perovskite solar cell, which includes a substrate, an NCQDs-TiO2 electron transport layer, a perovskite absorber layer, a hole transport layer, and a back electrode, which are sequentially disposed from the FTO conductive glass substrate side to the back electrode side.
[0099] The fabrication method of this perovskite solar cell includes: S1: Substrate pretreatment.
[0100] The FTO conductive glass was ultrasonically cleaned with deionized water, acetone, and isopropanol for 10 minutes each, then dried with nitrogen, and finally treated in an ultraviolet ozone treatment instrument for 10 minutes.
[0101] S2: Preparation of NCQDs-TiO2 electron transport layer.
[0102] S2-1: Preparation of nitrogen-doped carbon quantum dots: 1 g of citric acid and 0.4 g of urea were dissolved in 20 mL of deionized water and transferred to a high-pressure reactor lined with polytetrafluoroethylene. The reaction was carried out at 180 °C for 10 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature to obtain a dark brown aqueous solution of nitrogen-doped carbon quantum dots. Solid nitrogen-doped carbon quantum dot powder was obtained by dialysis and freeze-drying.
[0103] S2-2: Preparation of TiO2 precursor solution modified with nitrogen-doped carbon quantum dots: The TiO2 precursor solution (ethanol solution of isopropyl titanate, concentration of 0.12 mol / L) and the aqueous solution of nitrogen-doped carbon quantum dots (concentration of 0.5 mg / ml) were mixed at a mass ratio of 100:5 and ultrasonically treated for 25 min to uniformly disperse the nitrogen-doped carbon quantum dots in the TiO2 precursor solution.
[0104] S2-3: Preparation of the electron transport layer: A nitrogen-doped carbon quantum dot-modified TiO2 precursor solution was spin-coated onto the FTO substrate obtained in step S1 at a speed of 2800 r / min for 25 s. The substrate was then pre-calcined on a hot plate at 140 °C for 12 min to remove the solvent. Subsequently, it was annealed in a muffle furnace at 150 °C for 90 min to obtain a dense NCQDs-TiO2 electron transport layer with a thickness of approximately 20 nm.
[0105] S3: Prepare a perovskite light-absorbing layer.
[0106] 461 mg PbI₂ and 159 mg CH₃NH₃I were dissolved in 1 mL of a mixed solvent of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) (volume ratio 6.5:3.5), and stirred overnight to obtain a perovskite precursor solution. The perovskite precursor solution was spin-coated for 35 s at 3800 rpm in a nitrogen glove box. At the 25th second of spin-coating, 180 μL of chlorobenzene was rapidly added dropwise as an anti-solvent. Immediately after spin-coating, the sample was transferred to a 95°C hot plate for annealing for 15 min to obtain a dark brown perovskite film with a thickness of approximately 400 nm.
[0107] S4: Prepare the hole transport layer.
[0108] 72.3 mg of spiro-OMeTAD was dissolved in 1 mL of chlorobenzene, and 28.8 μL of 4-tert-butylpyridine and 17.5 μL of acetonitrile solution of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) (520 mg / mL) were added to prepare a hole transport layer solution. The solution was spin-coated at 3800 rpm for 25 s to obtain a hole transport layer with a thickness of approximately 100 nm.
[0109] S5: Prepare the metal electrode.
[0110] An 80 nm thick gold electrode was deposited on the surface of the hole transport layer using a thermal evaporation method.
[0111] Example 8 This embodiment provides a perovskite solar cell, which includes a substrate, an NCQDs-TiO2 electron transport layer, a perovskite absorber layer, a hole transport layer, and a back electrode, which are sequentially disposed from the FTO conductive glass substrate side to the back electrode side.
[0112] The fabrication method of this perovskite solar cell includes: S1: Substrate pretreatment.
[0113] The FTO conductive glass was ultrasonically cleaned with deionized water, acetone, and isopropanol for 20 minutes each, then dried with nitrogen, and finally treated in an ultraviolet ozone treatment instrument for 20 minutes.
[0114] S2: Preparation of NCQDs-TiO2 electron transport layer.
[0115] S2-1: Preparation of nitrogen-doped carbon quantum dots: 1 g of o-phenylenediamine and 0.6 g of ethylenediamine were dissolved in 20 mL of deionized water and transferred to a high-pressure reactor lined with polytetrafluoroethylene. The reaction was carried out at 220 °C for 5 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature to obtain a dark brown aqueous solution of nitrogen-doped carbon quantum dots. Solid nitrogen-doped carbon quantum dot powder was obtained by dialysis and freeze-drying.
[0116] S2-2: Preparation of TiO2 precursor solution modified with nitrogen-doped carbon quantum dots: The TiO2 precursor solution (isopropanol solution of tetraethyl titanate, concentration of 0.18 mol / L) and the aqueous solution of nitrogen-doped carbon quantum dots (concentration of 5 mg / ml) were mixed at a mass ratio of 100:5 and ultrasonically treated for 35 min to uniformly disperse the nitrogen-doped carbon quantum dots in the TiO2 precursor solution.
[0117] S2-3: Preparation of the electron transport layer: A nitrogen-doped carbon quantum dot-modified TiO2 precursor solution was spin-coated onto the FTO substrate obtained in step S1 at a speed of 3200 r / min for 35 s, followed by pre-calcination on a hot plate at 160 °C for 8 min to remove the solvent. Subsequently, it was annealed in a muffle furnace at 250 °C for 30 min to obtain a dense NCQDs-TiO2 electron transport layer with a thickness of approximately 100 nm.
[0118] S3: Prepare a perovskite light-absorbing layer.
[0119] 461 mg PbI₂ and 159 mg CH₃NH₃I were dissolved in 1 mL of a mixed solvent of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) (volume ratio 7.5:2.5), and stirred overnight to obtain a perovskite precursor solution. The perovskite precursor solution was spin-coated for 45 s at 4200 rpm in a nitrogen glove box. At the 25th second of spin-coating, 220 μL of chlorobenzene was rapidly added dropwise as an anti-solvent. After spin-coating, the sample was immediately transferred to a hot plate at 100 °C and annealed for 10 min to obtain a dark brown perovskite film with a thickness of approximately 600 nm.
[0120] S4: Prepare the hole transport layer.
[0121] 72.3 mg of spiro-OMeTAD was dissolved in 1 mL of chlorobenzene, and 28.8 μL of 4-tert-butylpyridine and 17.5 μL of acetonitrile solution of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) (520 mg / mL) were added to prepare a hole transport layer solution. The solution was spin-coated at 4200 rpm for 35 s to obtain a hole transport layer with a thickness of approximately 200 nm.
[0122] S5: Prepare the metal electrode.
[0123] An 80 nm thick gold electrode was deposited on the surface of the hole transport layer using a thermal evaporation method.
[0124] Comparative Example 1 The difference between this comparative example and Example 1 is that the electron transport layer does not contain NCQDs, but is only a TiO2 electron transport layer.
[0125] Comparative Example 2 The difference between this comparative example and Example 1 is that in the NCQDs-TiO2 electron transport layer, the mass ratio of N-doped carbon quantum dots to TiO2 is 0.05:100.
[0126] Comparative Example 3 The difference between this comparative example and Example 1 is that in the NCQDs-TiO2 electron transport layer, the mass ratio of N-doped carbon quantum dots to TiO2 is 10:100.
[0127] Comparative Example 4 The difference between this comparative example and Example 1 is that the carbon quantum dots are not doped with N.
[0128] Comparative Example 5 The difference between this comparative example and Example 1 is that the amount of N doping in the N-doped carbon quantum dots is 2wt%.
[0129] Comparative Example 6 The difference between this comparative example and Example 1 is that the amount of N doping in the N-doped carbon quantum dots is 20wt%.
[0130] Test case The perovskite solar cells prepared in Examples 1-8 and Comparative Examples 1-6 were placed in a glove box filled with high-purity nitrogen (purity >99.999%) (H2O <0.1ppm, O2 <0.1ppm) without encapsulation, and continuously irradiated with AM1.5G standard light (100mW / cm²) at room temperature (25±2℃). 2 The system operates in Maximum Power Point Tracking (MPPT) mode. A complete JV characteristic curve is tested every 100 hours, and the changes in Jsc, Voc, FF, and PCE are recorded. The results are shown in Table 1 and [Table data missing]. Figure 1 As shown in Table 1, the initial performance results are presented.
[0131] Table 1 Test Results
[0132] As can be seen from Table 1, the overall performance of the perovskite solar cells provided by the embodiments of the present invention is better than that of the comparative examples, and the effect of Example 4 is the best.
[0133] In addition, combined Figure 1As can be seen, the device without NCQDs in Comparative Example 1 had an initial PCE of 17.0%, which rapidly decreased to 14.5% (85% retention) within the first 200 hours, decreased to 11.6% (68% retention) after 500 hours, and decreased to 9.5% (56% retention) after 1000 hours. The device containing 1% NCQDs in Example 4 had an initial PCE of 21.5%, which slightly decreased to 20.8% (98% retention) within the first 200 hours, remained at 19.6% (92% retention) after 500 hours, and remained at 19.0% (89% retention) after 1000 hours.
[0134] In summary, this invention broadens the full-spectrum response range of the device by introducing NCQDs into the TiO2 electron transport layer and utilizing their upconversion luminescence properties. By forming Ti-OC covalent bonds between quantum dots and TiO2 at the interface, a stable and efficient electron transport channel can be constructed. Furthermore, it can reduce the electron injection barrier by precisely controlling energy level matching and suppress nonradiative recombination by passivating perovskite surface defects, thereby significantly improving the photoelectric conversion efficiency and long-term stability of perovskite solar cells, achieving the technical effect of improving device performance and stability.
[0135] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A perovskite solar cell, characterized in that, The perovskite solar cell includes an NCQDs-TiO2 electron transport layer disposed on the substrate surface, wherein the NCQDs-TiO2 electron transport layer contains Ti-OC covalent bonds formed by TiO2 and N-doped carbon quantum dots; In the NCQDs-TiO2 electron transport layer, the mass ratio of N-doped carbon quantum dots to TiO2 is 0.1:100 to 5:
100.
2. The perovskite solar cell according to claim 1, characterized in that, The NCQDs-TiO2 electron transport layer also has at least one of the following characteristics: Feature 1: In the N-doped carbon quantum dots, the N doping amount is 5wt%~15wt%; Feature 2: The thickness of the NCQDs-TiO2 electron transport layer is 20nm~100nm.
3. The perovskite solar cell according to claim 1, characterized in that, The perovskite solar cell further includes a perovskite light-absorbing layer, a hole transport layer, and a metal electrode; The perovskite light-absorbing layer is disposed on the surface of the NCQDs-TiO2 electron transport layer away from the substrate; the hole transport layer is disposed on the surface of the perovskite light-absorbing layer away from the NCQDs-TiO2 electron transport layer; and the metal electrode is disposed on the surface of the hole transport layer away from the perovskite light-absorbing layer.
4. The perovskite solar cell according to any one of claims 1 to 3, characterized in that, The perovskite solar cell has at least one of the following characteristics: Feature 3: The short-circuit current density of the perovskite solar cell is not less than 22.7 mA / cm². 2 ; Feature 4: The open-circuit voltage of the perovskite solar cell is not less than 1.08V; Feature 5: The fill factor of the perovskite solar cell is not less than 0.74; Feature 6: The photoelectric conversion efficiency of the perovskite solar cell is not less than 18%.
5. A method for preparing a perovskite solar cell according to any one of claims 1 to 4, characterized in that, Includes the following steps: A solution of nitrogen-doped carbon quantum dots modified TiO2 precursor was coated onto the substrate surface, followed by solvent removal and annealing.
6. The preparation method according to claim 5, characterized in that, The coating was applied by spin coating at a speed of 2800 r / min to 3200 r / min and a spin coating time of 25 s to 35 s. And / or, the solvent is removed by heating at a temperature of 140℃~160℃ for a time of 8min~12min; And / or, the annealing temperature is 150℃~250℃, and the annealing time is 30min~90min.
7. The preparation method according to claim 5 or 6, characterized in that, The preparation of a nitrogen-doped carbon quantum dot modified TiO2 precursor solution includes: dispersing nitrogen-doped carbon quantum dots in a TiO2 precursor solution; Preferably, dispersing nitrogen-doped carbon quantum dots in the TiO2 precursor solution includes: mixing the nitrogen-doped carbon quantum dot solution with the TiO2 precursor solution and then sonicating.
8. The preparation method according to claim 7, characterized in that, The solute in the TiO2 precursor solution includes at least one of isopropyl titanate and tetraethyl titanate, and the solvent includes at least one of ethanol and isopropanol. Preferably, the concentration of the solute in the TiO2 precursor solution is 0.12 mol / L to 0.18 mol / L.
9. The preparation method according to claim 7, characterized in that, The nitrogen-doped carbon quantum dot solution is an aqueous solution of nitrogen-doped carbon quantum dots, and the ratio of nitrogen-doped carbon quantum dots to water is from 0.5 mg:1 mL to 5 mg:1 mL.
10. The preparation method according to claim 9, characterized in that, The preparation of the nitrogen-doped carbon quantum dots includes: reacting a carbon source and a nitrogen source in the presence of water, dialyzing the reaction product, and drying it; Preferably, the carbon source includes at least one of citric acid and o-phenylenediamine; Preferably, the nitrogen source includes at least one of urea and ethylenediamine; Preferably, the mass ratio of the carbon source to the nitrogen source is 1:0.4 to 1:0.6; Preferably, the reaction temperature of the carbon source and the nitrogen source is 180℃~220℃, and the reaction time is 5h~10h.